2021
DOI: 10.1111/iej.13548
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with root canal treatment and outcomes in the Swedish public dental health service: A prospective cohort study

Abstract: Aim To document satisfaction with root canal treatment procedures and outcomes among patients treated at Swedish public dental clinics. Method The original material comprised 243 patients who began root canal treatment (RCT) at 20 public dental clinics in the county of Västra Götaland, Sweden. One to three years later, 236 (97.1%) were posted a questionnaire of eight items, rating patient perceptions of RCT completion, present pain intensity and satisfaction with the RCT. To evaluate the reliability of the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…This study presents a 1‐year detailed follow‐up after initiation of endodontic therapy based on patient records. Patient satisfaction with root canal treatment has also been studied based on a patient‐focused questionnaire (Wigsten et al, 2021)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study presents a 1‐year detailed follow‐up after initiation of endodontic therapy based on patient records. Patient satisfaction with root canal treatment has also been studied based on a patient‐focused questionnaire (Wigsten et al, 2021)…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study (Wigsten et al, 2021), the patients' perceptions of their treatment were examined. One to 3 years after starting RCT, patient satisfaction was generally ranked as high, despite the loss or incomplete treatment of 30% of the teeth and reports of present pain by half the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not the quality of dental care, but how the patient perceives the dental care can be assessed, and in general, patients are satisfied with the outcome of root canal treatment (28,29). A recent study showed that patients who underwent nonsurgical retreatment reported significant time loss from work but lower physical and psycho-social disability during the recovery phase in comparison to apical surgery (30).…”
Section: Resultsmentioning
confidence: 99%